A Model of Fatigue Following Traumatic Brain Injury. Issue 4 (July 2015) - Ponsford, Jennie; Schönberger, Michael; Rajaratnam, Shantha M. W.
Abstract : Objective: Fatigue is one of the most frequent sequelae of traumatic brain injury (TBI), although its causes are poorly understood. This study investigated the interrelationships between fatigue and sleepiness, vigilance performance, depression, and anxiety, using a structural equation modeling approach. Methods: Seventy-two participants with moderate to severe TBI (78% males) were recruited a median of 305 days postinjury. They completed the Fatigue Severity Scale, a vigilance task, the Epworth Sleepiness Scale, and Hospital Anxiety and Depression Scale. A model of the interrelationships between the study variables was developed, tested, and modified with path analysis. Results: The modified model had a good overall fit (χ 2 2 = 1.3, P = .54; comparative fit index = 1.0; root-mean square error of approximation = 0.0; standardized root-mean square residual = 0.02). Most paths in this model were significant ( P < .05). Fatigue predicted anxiety, depression, and daytime sleepiness. Depression predicted daytime sleepiness and poor vigilance, whereas anxiety tended to predict reduced daytime sleepiness. Conclusions: This model confirms the complexity of fatigue experience. It supports the hypothesis that fatigue after TBI is a cause, not a consequence, of anxiety, depression, and daytime sleepiness, which, in turn (especially depression), may exacerbate fatigue by affecting cognitive functioning. These findings suggest that to alleviate fatigue, it is important to address each of these factors. However, the findings need to be confirmed with a longitudinal research design.